RANCANG BANGUN APLIKASI LATIHAN SOAL UJIAN NASIONAL SEKOLAH MENENGAH UMUM (Information Technology and Telematics, 2013)
With advances in information technology arerapidly evolving in the era of globalization, many problems -problems that arise in information technology and also did notrule out a lot of ideas - new ideas about information technologyIn this case I want to design an application in the form of a national exam practice web-based, which is the purpose of theexercise of this national exam, which is to facilitate internetusers particularly high school students who want to face thenational exam in its efforts to prepare for practice by doingpractice questions exam through access to the Internet isgrowing rapidly today. Software used for the manufacture ofthis application is comprised of the PHP programming language supported by Adobe Dreamweaver CS5 as a texeditor, and to use the MySQL database management. With thiscollection of exercises apilkasi national exam for a web-based school learning system for students - high school student in thelearning process and prepare for the national exam by utilizingthe internet. Keywords : National Test, PHP, MySQL, Dreamweaver